AÇÕES DE FORMAÇÃO CONTINUADA PARA OS PROFESSORES DA EDUCAÇÃO INFANTIL NA REDE MUNICIPAL DE TOCANTINÓPOLIS NO PERÍODO DE 2016-2021 - Zilma, Ferreira De Oliveira (Universidade Federal do Tocantins, 2022)
The article aims to analyze the continuing education actions developed with Early Childhood Education teachers working in the municipal network of Tocantinópolis, from 2016 to 2021, in the light of the following documents: National Common Curricular Base (BNCC); Tocantins Curricular Document (DCT) and the Municipal Education Plan (PME). Having as type of research the documentary with a qualitative approach. The data production materials consisted of slides, reports and frequencies produced during the actions of continuing education in the investigated educational reality, a bibliographic survey was also carried out to support the theme and a survey on official websites, seeking legal documents that guide the organization of Early Childhood Education in its various dimensions. In view of the analyses, it is understood that the training focuses on actions that enable teachers to develop the goals guided by the documents, it is a preparation for the operationalization of what is provided by them, with a gap being observed regarding the critical positioning of the participants in what is being discussed. refers to the debate on the very form of structuring and institutionally directed referrals. It is concluded that it is still a great challenge to talk about continuing education, according to its structures aligned with these documents, as in the BNCC that situates contemporary debates in the educational field.